The zonation of coastal dune plants in relation to sand burial, resource availability and physiological adaptation - Gilbert, Matthew Edmund (Rhodes University, Faculty of Science, Botany Department, 2008)
When considering the large amount of work done on dune ecology, and that a number of the classical ecological theories originate from work on dunes, it is apparent that there remains a need for physiological and mechanistic explanations of dune plant phenomena. This thesis demonstrated that in the extreme coastal environment dune plants must survive both high rates of burial (disturbance), and low nutrient availability (stress). The ability of four species to respond to these two factors corresponded with their position in a vegetation gradient on the dunes. A low stem tissue density was shown to enhance the potential stem elongation rate of buried plants, but reduced the maximum height to which a plant could grow. Such a tradeoff implies that tall light-competitive plants are able to survive only in stable areas, while burial responsive mobile-dune plants are limited to areas of low vegetation height. This stem tissue density tradeoff was suggested as the mechanism determining the zonation that species show within the dune vegetation gradient present at various sites in South Africa. Finally, detailed investigations of dune plant ecophysiology found that: 1) The resources used in the response to burial derive from external sources of carbon and nitrogen, as well as simple physiological and physical mechanisms of resource allocation. 2) The leaves of dune plants were found to be operating at one extreme of the photosynthetic continuum; viz efficient use of leaf nitrogen at the expense of water loss. 3) Contrary to other ecosystems, the environmental characteristics of dunes may allow plants to occupy a high disturbance, high stress niche, through the maintenance of lowered competition. 4) At least two mobile-dune species form steep dunes, and are able to optimise growth, on steeper dunes, such that they have to grow less in response to burial than plants that form more shallow dunes. In this thesis, it was shown that the link between the carbon and nitrogen economies of dune plants was pivotal in determining species distributions and survival under extreme environmental conditions. As vast areas of the world's surface are covered by sand dunes these observations are not just of passing interest.
Keywords: Sand dune conservation -- South Africa -- Eastern Cape; Coastal ecology -- South Africa -- Eastern Cape; Botany -- South Africa -- Eastern Cape; Coastal biology -- South Africa -- Eastern Cape; Littoral plants -- South Africa -- Eastern Cape; Littoral plants; Sand dune plants -- Ecophysiology; Sand dune plants -- Geographical distribution